Automated mail delivery robot using GPS navigation - Mudiyanselage, Supun Sandaru R.R.; Than Lin; Bohez, Erik L.J. (Pathum Thani : Asian Institute of Technology, 2017)
The development of artificial intelligence in locomotive robots and its combination with the fields of mechanical and electronic engineering has led to development of many efficient robots. This report will present a robotic solution to the application of transportation of small scale packages such as envelops. This can be used as a both indoor and outdoor application. Here the robot on its own will navigate to any location given as GPS coordinates.it can tackle mildly challenging terrain and detect obstacles ahead. The key features of this project will be obstacle avoidance, location awareness, bearing identification, GPS coordinate reading, communication with an android device.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Global Positioning System -- Navigation; Robotics